Problematika Hukum Penyelesaian Sengketa Terhadap Diskriminasi Hak Pekerja Wanita Pada Persyaratan Kerja Di Pasar Swalayan - Karamoy, Roy V.; Simbala, Yumi; Gosal, Vecky (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
This research was conducted with the aim of finding out how to resolve disputes regarding discrimination against the rights of female workers in terms of employment in supermarkets. The two problems are the application of employment requirements to the rights of female workers and the prevention of discrimination in law. All of this is reviewed from Law No. 13 of 2003 concerning Manpower (UUTK) and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes (UUPPHI). By utilizing empirical legal research methods with designated informants. Discrimination of the rights of female workers in terms of employment in supermarkets can occur. All legal efforts to prevent discrimination against the rights of female workers in supermarkets have been adjusted to the norms of life that are based on respect for human rights and applicable laws.